Perbandingan Kotowaza yang Mengandung Kata "Inu" dengan Padanan dalam Peribahasa Indonesia - Raharjo, Reiki Rahendra; Puspitosari, Dwi (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2025)
Kotowaza or proverbs in Japanese are figurative sentences used as teaching or satire. Some Kotowazas have similar meanings to Indonesian proverbs, and similarities and differences are caused by cultural, historical, and demographic factors. This study is 1) to find out the equivalent meaning of Japanese Kotowaza containing the element inu in Indonesian proverbs and 2) to describe the factors that influence the differences between Kotowaza containing the element "inu" and the equivalent in Indonesian proverbs. The data source used is "Shin-meikai Dongeng and Kotowaza Dictionary edition 2," published by the Sanseidou editorial office, with data in the form of Kotowaza containing the element inu (çŠ¬) or dog. The theory used in this study is the theory of language variety put forward by Subarianto (2000), which mentions several factors that cause the emergence of language diversity, namely cultural, historical, and demographic factors. The research method used is descriptive qualitative, with the focus of research on all Kotowaza (Japanese proverbs) containing the element "inu." The data collection technique used documentation techniques and contrastive analysis techniques. From the results of the study, it is known that from 73 Japanese Kotowaza containing the element "inu," 15 data were found that have equivalent proverbs in Indonesian, with the difference being that animals appear to replace inu, such as monkeys, tadpoles and crocodiles, and equivalents that do not appear animals at all. Of the 15 Kotowazas, it is known that there are factors that influence the equivalent between Japanese Kotowaza and Indonesian proverbs; namely, 5 data are influenced by one factor, two factors influence 8 data, and one factor influence 2 data. This finding concludes that cultural factors always appear in 15 Japanese Kotowaza data with equivalents in Indonesian proverbs. Keywords: equivalent prover; inu; Japanese language; kotowaza